The Effect Of Liquidity, Dividend Policy, Profitability, And Company Size On The Value Of Manufacturing Companies Listed In The Jakarta Islamic Index (JII) Year (2020–2024) - Anjas Irawan; Ahmad Syahrizal; Achyat Budianto (Citakonsultindo, 2026)
This study aims to analyze the influence of liquidity, dividend policy, profitability, and company size on company value in manufacturing companies listed in the Jakarta Islamic Index (JII) in 2020-2024. In this study, a quantitative method was used and the analysis method used was multiple regression of panel data with the help of the eviews program 12. The data of this study is secondary data. The data collection technique uses financial statements registered on the IDX website with purposive sampling techniques. The results of the study show that it partially shows that liquidity (X1) partially has no effect on the company's value (Y), this is proven by the company's value of 0.1503 > 0.05. The dividend policy (X2) partially has no effect on the company's value (Y), this is evidenced by showing the company's value of 0.1693 > 0.05. Profitability (X3) partially affects the value of the company (Y), this is proven to show a probability value of 0.0010 < 0.05. The size of the company (X4) partially affects the value of the company (Y), this is proven by showing a probability value of 0.0074 < 0.05. The results of simultaneous hypothesis testing showed that liquidity, dividend policy, profitability and company size had an influence on the company's value.